Introducing an effective curing method for mortar containing high volume cementitious materials - Aprianti, E.; Shafigh, P.; Zawawi, R.; Abu Hassan, Z.F. (Elsevier, 2016)
This study reported an on-going research project of producing sustainable construction material for pre-cast industry. This paper studies the physical and chemical properties of materials, compressive strength, flexural strength, water absorption and porosity of multi blended cements under different curing methods. Fly ash (FA), ground granulated blast furnace slag (GGBFS) and rice husk ash (RHA) were used to replace with 50% ordinary Portland cement by mass. Specimens were cured in water (WC), air under room temperature (AC), the combination of hot-water at 60 °C for 24 h followed by curing in water (HWC), and air (HAC). The results showed that HAC could be an effective curing method with higher compressive and flexural strengths, lower water absorption and porosity for blended cement mortars. Mortars containing GGBFS in binder had higher enhancement on compressive strength under early hot water curing. While, at 24 h hot water curing mortar containing OPC-RHA-FA binder showed better quality in properties compared to the other binders.